The presence of Helicobacter pylori in oral cavities of patients with leukoplakia and oral lichen planus - Magdalena Kazanowska-Dygdała; Irena Duś; Małgorzata Radwan-Oczko (University of São Paulo, 2016)
ABSTRACT Objective Helicobacter pylori infection is one of the most common bacterial infections in men. This gastrointestinal pathogen is closely related to gastritis, peptic ulcers, and the increased risk of gastric cancer. Numerous studies have indicated oral cavities as possible Helicobacter pylori reservoirs. Helicobacter pylori has been detected both in supragingival and subgingival plaques, and also in saliva. In addition, the relationship between lesions of oral mucosa and the presence of H. pylori has been evaluated and described in some studies. The aim of this study was to assess the presence of Helicobacter pylori DNA in the oral cavity of patients with oral leukoplakia and oral lichen planus. Material and Methods The study included 54 patients with oral leukoplakia, 72 with oral lichen planus lesions, and 40 healthy controls. The presence of Helicobacter pylori in oral cavity samples was analyzed using a single-step Polymerase Chain Reaction (PCR) method. All patients underwent a periodontal examination and the following clinical parameters were collected: pocket depth, bleeding, and plaque indexes. The periodontal status was assessed using the Offenbacher classification. Results In most patients, pathological lesions were in typical sites on the buccal mucosa (leukoplakia in 88%, and oral lichen planus in 93% of patients). The DNA of the Helicobacter pylori was present in 20% of patients with leukoplakia and 23% of patients with lichen planus. We did not find the DNA of H. pylori in healthy controls. The periodontal status described by periodontal indices was worse in the investigated group than in the control group. Conclusion These findings suggest that the H. pylori presence in oral cavities may be related with leukoplakia and lichen planus oral lesions.